PENGARUH MANAJEMEN RISIKO KREDIT DAN FAKTOR SPESIFIK BANK TERHADAP KINERJA KEUANGAN BANK KONVENSIONAL DI BEI - Cyntia Monalisa Hutauruk; Susy Muchtar; Agnessa Britannia Paragina (Jurnal Pendidikan Ekonomi (JURKAMI), 2022)
This study was conducted to analyze the potential for bad credit management and bank-specific factors on bank financial performance. The method used to obtain the sample is purposive sampling and the method used to analyze the data is using panel data regression. The independent variables used to identify the bad impact of credit in this study are NPL and the ratio of capital adequacy (CAR), while the cost efficiency ratio (CER), the average loan interest rate (ALR), and the liquidity ratio (LR) which measure specific factors bank as well as bank size and inflation as control variables. On the other hand, financial performance is identified by return on assets (ROA) and return on equity (ROE). The results of this research can help bank financial managers to improve financial performance by paying attention to credit risk management, taking appropriate techniques efficiently in providing loans and seeing liquidity position as a factor